2020
DOI: 10.1186/s12883-020-01986-9
|View full text |Cite
|
Sign up to set email alerts
|

Complex intracranial vascular complications caused by essential thrombocythemia: a critical case report

Abstract: Background Essential thrombocythemia (ET) is a myeloproliferative neoplasm characterized by elevated and dysfunctional platelets. ET can result in systemic thrombotic and hemorrhagic complications, and it’s a rare cause of stroke. The coexistence of multiple vascular lesions has seldom been reported in patients with essential thrombocythemia. Case presentation A young woman presented with isolated and persistent vertigo and vomiting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The pathogenesis of hemorrhagic stroke in ET has not yet been fully elucidated. Previous studies have suggested that hemorrhagic complications of ET are associated with a highly elevated platelet count (> 1,000,000/mL) and are often associated with acquired Von Willebrand syndrome [ 5 , 7 ]. However, in both cases, the platelet count was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of hemorrhagic stroke in ET has not yet been fully elucidated. Previous studies have suggested that hemorrhagic complications of ET are associated with a highly elevated platelet count (> 1,000,000/mL) and are often associated with acquired Von Willebrand syndrome [ 5 , 7 ]. However, in both cases, the platelet count was low.…”
Section: Discussionmentioning
confidence: 99%
“…Patient management includes antiplatelet and cytoreductive therapy, as in the current case. Only a few published case reports of intracerebral hemorrhage in patients with ET and JAK2 V617F mutations exist [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%